Tendinopatia patelar : biomecânica da aterrissagem de salto, déficits de força e flexibilidade e efeitos de intervenções de tratamento enfocando fatores proximais da cadeia cinética em atletas - Silva, Rodrigo Scattone da (2016)
Patellar tendinopathy (PT) is one of the most common causes of knee pain in athletes. The prevalence of PT in elite volleyball athletes can be as high as 45%. Studies assessing lower limb muscles strength and flexibility and trunk and lower limb biomechanics during sports related activities are scarce. Also, the effects of interventions focusing on jump-landing strategy modifications to reduce the overload in the knee joint in athletes with PT have not yet been investigated. The purposes of this Thesis were: to compare hip, knee and ankle torques, as well as knee and ankle flexibility between athletes with and without PT; to compare trunk and lower limb sagittal plane biomechanics during jump-landings between athletes with and without PT; to verify the effects of an intervention of hip muscles strengthening and jump-landing strategy modification on pain, function and lower limb biomechanics in a volleyball athlete with PT and; to verify the immediate effects of changing sagittal plane trunk position on lower limb biomechanics and knee pain during jump-landings in athletes with and without PT. For the isometric torque evaluations, a handheld dynamometer was used. An inclinometer was used for the flexibility tests. For the landing biomechanics evaluations, motion capture systems and force platforms were used. The athletes’ pain and disability were assessed by means of a visual analogue scale and the Victorian Institute of Sport Assessment-Patella questionnaire. Results showed that the athletes with PT presented lower hip extensor torque and lower hamstrings and ankle flexibility when compared to healthy athletes. In the biomechanical evaluation, athletes with PT displayed less hip flexion during jump-landings and smaller contribution of the hip joint for dissipation of the landing forces when compared to healthy athletes. The eight-week intervention composed by hip strengthening exercises and jump-landing strategy modification decreased pain and disability and improved lower limb biomechanics during jump-landing in an athlete with PT, both in short and long term. Finally, increasing trunk flexion during jump-landings produced immediate effects of: 1) reducing peak patellar tendon force in athletes with and without PT; 2) reducing knee pain during landings in athletes with PT. Proximal factors of the kinetic chain, such as hip strength and hip/trunk movements during jump-landings, should not be overlooked in the development of interventions for the rehabilitation of athletes with PT.